New procognitive enhancers acting at the histamine H3 and AMPA receptors reverse natural forgetting in mice: comparisons with donepezil and memantine in the object recognition task. Issue 4 (June 2019) - Louis, Caroline; Llopis, Karine; Danober, Laurence; Panayi, Fany; Lestage, Pierre; Beracochea, Daniel
Abstract : This study evaluated the procognitive effects of S 38093 (a new inverse agonist of the histaminergic H3 receptor) and S 47445 (a new α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) in 2–3-month-old Swiss mice as compared with donepezil and memantine, two main reference compounds in the treatment of Alzheimer's disease. The object recognition task allows the study of natural forgetting and is classically used in assessing drug effects on memory. Here, we show that mice exhibit significant object recognition at short (15 min) but not long (24 h) retention intervals separating the familiarization and recognition phases. S 47445 (1.0, 3.0, and 10.0 mg/kg) and S 38093 (0.3, 1.0, and 3.0 mg/kg), both administered postoperatively, 1 h before familiarization and recognition sessions, rescued memory at the long retention interval; their memory-enhancing effects were as powerful as those obtained with donepezil or memantine (1.0 and 3.0 mg/kg for both compounds). Thus, S 38093 and S 47445, detected as positive controls in the object recognition task, are promising compounds for the treatment of amnesic syndromes.